Platformising Informal Motorcycle Transport, Youth Livelihoods, and Digital Constraints: A Case of ORide E-Hailing in Ibadan, Nigeria - Samson, Ingomowei Preye; Iwelu , Michael Obinna (Transportation Development Research, 2025)
The platform-based motorcycle ride-hailing is changing informal mobility systems in African urban areas, but there is little empirical data on the socio-economic effects, adoption forces, and challenges of sustainability. This paper examines the rise of ORide, a commercial motorcycle e-hailing service in Ibadan, Nigeria, and what this means to mobility, the livelihood of young people, and how informal transport is being transformed. The study employs a mixed-methods design with 250 ORide riders and 100 clients and supplements it with in-depth interviews to investigate the reasons to join an ORide, the perceived benefits, constraints faced by clients and users, and the influence of factors on the sustainability of the platform. The findings indicate that ORide can offer better access to mobility, regular income opportunities, and a more formalised identity to riders, although the key constraints were identified, such as low network connectivity (92%), mobile data unreadability (84%), unreliable electricity provision (76%), unavailability of smartphones (55%), and regulatory unpredictability. It contributes novel insights on how socio-economic strain and digital constraints shape participation in motorcycle e-hailing in a developing-city context, grounded by integrating Strain Theory and TAM to clarify rider motivations, platform adoption, and the sustainability of platformised informal transport systems.